Surveying emigrants worldwide–using Facebook and Instagram to recruit respondents in cross-national (e)migration research - Steffen Pötzschke; Bernd Weiß (Comparative Migration Studies)
Abstract Sampling remains a major challenge when researching minority populations, especially in cross-national settings. While various sampling methods are established in the field, most of them cannot easily be implemented globally. However, worldwide operating Social Networking Sites provide an opportunity for the recruitment of certain hard-to-reach populations in almost all countries. Targeting German emigrants through paid advertisements on Facebook and Instagram, we aim to ascertain whether such ads could be used to recruit a nonprobability emigrant sample on a global scale. Specifically, we look at two aspects: relative cost efficiency and coverage. Using this approach, we achieved 3,816 completed surveys from emigrants in 148 countries and territories. The method also yielded good results in world regions where other surveys faced severe coverage issues. Furthermore, a considerable share of the sample could not have been reached using German population registers as a sampling frame, which otherwise constitutes the most promising alternative approach.